Discourse Pragmatics and Language Variation - Sashka Jovanovska, PhD; Marija Tashkoska, M.A (Academia One Publishing, 2023)
This paper explores the relationship between pragmatics and language variation in English language. It begins by defining the concepts of pragmatics and language variation and the factors that influence language variation. The main part of the paper discusses the role of pragmatics in language variation and how pragmatic factors such as context, culture, and social norms influence language use. The paper also examines the impact of language variation on communication and the potential for miscommunication due to differences in pragmatic understanding. The conclusion highlights the need for language learners to understand the role of pragmatics in language variation and for educators to incorporate pragmatic instructions into language teaching programs.
Keywords: pragmatics; discourse analysis; context; discourse pragmatics